Do Management Interventions Last? : Evidence from India - Bloom, Nicholas; Mahajan, Aprajit; McKenzie, David; Roberts, John (World Bank, Washington, DC, 2018)
Beginning in 2008, the authors conducted a randomized controlled trial that changed management practices in a set of Indian weaving firms (Bloom et al. 2013). In 2017 the plants were revisited and the authors found three main results. First, while about half of the management practices adopted in the original experimental plants had been dropped, there was still a large and significant gap in practices between the treatment and control plants. Likewise, there remained a significant performance gap between treatment and control plants, suggesting lasting impacts of effective management interventions. Second, while few management practices had demonstrably spread across the firms in the study, many had spread within firms, from the experimental plants to the non-experimental plants, suggesting limited spillovers between firms but large spillovers within firms. Third, managerial turnover and the lack of director time were two of the most cited reasons for the drop in management practices in experimental plants, highlighting the importance of key employees.